43 THE ROLE OF PROTEIN PHOSPHATASE 2A IN THE REGULATION OF ENDOTHELIAL CELL CYTOSKELETON STRUCTURE. (1st March 2006) - Tar, K.; Csortos, C.; Czikora, I.; Olah, G.; Ma, S-F.; Wadgaonkar, R.; Gergely, P.; Garcia, J. G.N.; Verin, A. D.
Abstract : Our recently published data suggested the involvement of protein phosphatase 2A (PP2A) in endothelial cell (EC) barrier regulation (Tar et al, 2004). In order to further elucidate the role of PP2A in the regulation of EC cytoskeleton and permeability, PP2A catalytic (PP2Ac) and A regulatory (PP2Aa) subunits were cloned and human pulmonary arterial EC (HPAEC) were transfected with PP2A mammalian expression constructs or infected with PP2A recombinant adenoviruses. Immunostaining of PP2Ac or of PP2Aa+c overexpressing HPAEC indicated actin cytoskeleton rearrangement. PP2A overexpression hindered or at least dramatically reduced thrombin- or nocodazole-induced F-actin stress fiber formation and microtubule (MT) dissolution. Accordingly, it also attenuated thrombin- or nocodazole-induced decrease in transendothelial electrical resistance indicative of barrier protection. Inhibition of PP2A by okadaic acid abolished its effect on agonist-induced changes in EC cytoskeleton; this indicates a critical role of PP2A activity in EC cytoskeletal maintenance. The overexpression of PP2A significantly attenuated thrombin- or nocodazole-induced phosphorylation of HSP27 and tau, two cytoskeletal proteins, which potentially could be involved in agonist-induced cytoskeletal rearrangement and in the increase of permeability. PP2A-mediated dephosphorylation of HSP27 and tau correlated with PP2A-induced preservation of EC cytoskeleton and barrier maintenance. Collectively, our observations clearly demonstrate the crucial role of PP2A in EC barrier protection. Grant sponsor: National Heart, Lung, and Blood Institutes; grant numbers: HL67307, HL68062, HL58064; grant sponsor: Hungarian Science Research Fund; grant number: OTKA T043133.